La topografia y el hidroperiodo: dos factores que condicionan la restauracion de los humedales costeros - Flores Verdugo, F.=700 1 Moreno Casasola, P.; Agraz Hernandez, C.M.
(Es, En)
Ilus., 51 ref.
Keywords: ECOLOGIA FORESTAL; TOPOGRAFIA; INUNDACION; DURACION; MANGLES; SALINIDAD; FANGO; MEXICO; HUMEDALES